2020
DOI: 10.5152/eurjrheum.2020.20038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the correlation between disease activity score 28 and its ultrasonographic equivalent in rheumatoid arthritis patients

Abstract: The aim of the European Journal of Rheumatology is to cover various aspects of rheumatology for its readers, encompassing the spectrum of diseases with arthritis, musculoskeletal conditions, autoinflammatory diseases, connective tissue disorders, osteoporosis, translational research, the latest therapies and treatment programs. European Journal of Rheumatology publishes original articles, invited reviews, case based reviews, letters to the editor and images in rheumatology. The publication language of the jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the real-world setting, the presence or absence of US inflammation has been widely used to help rheumatologists with decision-making on continuing or switching the cs/b/tsDMARD, being especially useful in patients with a low SJC and DAS-28-CRP pointing to only moderate disease, because SJC was shown to be closely related to US synovitis and a high SJC may suggest a higher likelihood of PIRRA status. 35 Our study had some limitations. Firstly, although, all patients met the three essential EULAR criteria for D2T-RA, as a crosssectional study based on EMR, patients that would be considered D2T-RA because of (1) difficulty tapering down corticosteroids under 7.5 mg were not included because of incomplete, data including primary care corticosteroid data; (2) rapid radiographic progression because routine follow up radiographs is not part of our standard of care; and (3) RA symptoms deemed to impair quality of life as documented by either patient or physician, were not included.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the real-world setting, the presence or absence of US inflammation has been widely used to help rheumatologists with decision-making on continuing or switching the cs/b/tsDMARD, being especially useful in patients with a low SJC and DAS-28-CRP pointing to only moderate disease, because SJC was shown to be closely related to US synovitis and a high SJC may suggest a higher likelihood of PIRRA status. 35 Our study had some limitations. Firstly, although, all patients met the three essential EULAR criteria for D2T-RA, as a crosssectional study based on EMR, patients that would be considered D2T-RA because of (1) difficulty tapering down corticosteroids under 7.5 mg were not included because of incomplete, data including primary care corticosteroid data; (2) rapid radiographic progression because routine follow up radiographs is not part of our standard of care; and (3) RA symptoms deemed to impair quality of life as documented by either patient or physician, were not included.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, these patients may not benefit from b/tsDMARD cycling, because of the absence of inflammation. In the real‐world setting, the presence or absence of US inflammation has been widely used to help rheumatologists with decision‐making on continuing or switching the cs/b/tsDMARD, being especially useful in patients with a low SJC and DAS‐28‐CRP pointing to only moderate disease, because SJC was shown to be closely related to US synovitis and a high SJC may suggest a higher likelihood of PIRRA status 35 …”
Section: Discussionmentioning
confidence: 99%
“…2 patients (3.45%) in remission (DAS28≤2.6), 4 (6.9%) had low activity disease (2.6<DAS28≤3.2), 29 (50%) had moderate disease activity (3.2<DAS28≤5.1), and 23 (39.65%) had high activity disease (DAS28 >5). [14] The study in 2015 found that the duration of RA disease was 11 years and DAS-28(ESR) respectively significant higher from DAS28 (CRP) (4.0 vs 3.5; p < 0.001) and its value permanent higher after stratification based on age, gender, duration of the disease, and rheumatoid factor. [13] Research found that RA patients were dominated by women (93%); and some patient had duration of ten years disease and the mean DAS-28 score was 4.8.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be important to determine whether the pain is driven predominantly by disease activity or by changes in the central pain regulatory mechanisms. Recent evidence indicates that the number of swollen joints, rather than tender joints, is positively correlated with US-assessed joint inflammation [11][12][13][14]. Furthermore, negative correlations have been observed between tender joint counts and pressure pain thresholds (PPTs) measured at remote locations, suggesting alterations in central pain mechanisms [15][16][17].…”
Section: Key Messagesmentioning
confidence: 99%